A review of health management information system in the Kumasi Metropolis with respect to operations in the Pharmacy Department - Opare-Addo, Mercy Naa Aduele (Mrs) (2011)
A thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Science degree in Health Services Planning and Management,